Extending the vase life of mixed flower bouquets - Suntipabvivattana, Niramon (Cranfield University, 2012)
The popularity of mixed flowers bouquets has increased in the cut flower industry. The longevity of mixed flowers bouquets is limited by the individual life of each flower in the bunch. Various factors have been studied for their effect on the individual life of each flower in mixed flowers bouquets. The results indicate that the differences in vase life of each flower in mixed bouquets may come from the influence of their phenotype. In cut rose flowers, there were various contents of fructose, glucose, sucrose and myo-inositol in all cultivars. However, levels of sugars contents were not related to the long-lived cultivars. For cut lily flowers, the contents of fructose, glucose and sucrose were measured in the primary and the secondary bud of ‘Tiber’ lilies. Differences in the contents of fructose, glucose and sucrose between the primary and secondary bud, did not relate to the longevity of individual bud life. However, this experiment found increases in sucrose contents in both positions before the time of opening. This increase in sucrose may relate to the role of the carbohydrate energy source for bud opening. Bacteria found in this study seemed to be largely specific to different flower types. Also, species of bacteria found in the vase water of mixed flowers were less than in that of single varieties. Difference in species of bacteria may be due to differences between plants, and the conditions they exert in the vase water. In general bacterial numbers were high at the beginning of all the experiments, indicating a strong inoculum effect from stems, although there was no straightforward relationship between stem numbers and inoculum size, in all cases. Experiments of single varieties were studied using ‘Tiber’ lily, ‘Akito’ rose and ‘Valentino’ rose. The results indicated that the addition of stems did not result in higher numbers of bacteria, but vase life was reduced, especially for the roses. The effect of number of stems in mixed flowers was investigated in distilled water and liquid flower food. The result of the addition of stems was to reduce the vase life of both ‘Tiber’ lily and ‘Akito’ rose. However, the effect of more stems of ‘Akito’ roses had a greater effect on vase life, fresh weight and water uptake than in ‘Tiber’ lilies. This indicated that ‘Akito’ roses had a greater response to high bacteria populations than lilies. The role of chemical exudates on flowers was not clear in the present study as they only had an effect during the early part of the vase life. The vase lives of ‘Tiber’ lilies and ‘Akito’ roses in all treatments were not significantly different. Perhaps treatment effects caused by the presence of chemical exudates may have been ‘masked’ by the presence of micro-organisms. The screening of 12 essential oils (West Indian bay, cinnamon leaf, clove bud, clove leaf, Chinese ginger, lemongrass, mandarin, rosemary, sage, spearmint, sweet fennel, and thyme) showed that thyme oil and lemongrass oil are effective against more bacterial species over other essential oils. The comparison of the minimal bactericide concentration (MBC) of thyme oil and lemongrass oil showed that the average MBC for thyme oil was lower than that of lemongrass. However, the thyme oil failed to extend the vase life of ‘Tiber’ lily and ‘Akito’ rose. Thyme oil was effective against bacteria for a very short time and could not extend vase life, especially that of the ‘Akito’ rose. Overall, thyme oil treatment appeared to reduce vase life. The efficacy of nine weak organic acids was studied in vivo for their effect on six bacterial species. Bacterial samples were inoculated on trypticase soya agar (TSA) pH 4 and 7. At pH 7, the TSA was prepared by using distilled water. All six bacteria species grew well under these conditions. The results of weak organic acids studied at pH 7 showed that Trans-cinnamic acid was the only weak organic acid that could act against some bacteria. At pH 4, only L8 (Bacillus spp.) could grow, and Trans- cinnamic acid was effective against this bacteria. The initial result of testing Trans- cinnamic acid against bacteria offered some promise for it to be applied successfully to the vase water of cut flowers, in combination with buffer systems.